PENDIDIKAN KARAKTER DALAM PROSES PEMBELAJARAN MATEMATIKA DI KELAS XI MAN MODEL BANDA ACEH - Cut Nurul Fahmi; Nasruddin Nasruddin; Fithri Angelia Permana (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
Character education is education that develops and instills national character in students so that they have values and character as their own character, apply these values in their own lives, as members of society, and citizens who are religious, nationalist, productive, and creative. The purpose of this study was to determine the process of character education that is integrated with Mathematics learning for class XI MAN Model Banda Aceh. Respondents included principals of madrasahs, wakasek in the curriculum field, teachers of Mathematics subjects, and XI grade students. Data collection methods used were observation, interviews, and documentation. The research data was tested with a qualitative descriptive method to determine the Character Education in the Mathematics Learning Process of Class XI MAN Model Banda Aceh. The results showed that the integration of character education was carried out in the form of learning process activities. The model used is the Cooperative Learning model because it shows character values such as cooperation, responsibility, never giving up, working hard. The integration of character education in the Mathematics learning process in the MAN Model Banda Aceh is carried out starting from the planning, implementation, and evaluation stages of learning where the character values instilled and developed by mathematics teachers are religious, disciplined, honesty, unyielding, curiosity height and responsibility